KONSTRUKSI MASYARAKAT PERBANKAN TENTANG IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KABUPATEN LUMAJANG - Mustinka, Arinda Nuril (Paradigma, 2022)
Abstract The problem of poverty is a social phenomenon in all provinces, districts or cities in Indonesia. The government has been working with various policies and plans directly and indirectly to alleviate poverty. One of the government programs that aims to break the chain of poverty is Raskin. In its development, according to the president’s direction, all social assistance and subsidies are distributed non-cash and use the banking system to make it easier to control, and reduce the practice of irregularities. Therefore, in 2017 the Rastra program turned into non-cash food assistance (BPNT). The Lumajang government related to the implementation of BPNT, there were problems in the implementation of BPNT, namely a case of fraudulent. Non-Cash Food Aid (BPNT) funds This research method uses a qualitative approach by examining the informant, namely KPM. The results of this study indicate that the Himbara bank provides information counseling to KPM Klakah Subdistrict and Kedungjajang District regarding the procedure for electronically disbursing social assistance which is carried out through E-Warong. The implementation of the Non-Cash Food Assistance (BPNT) program for the community in Lumajang, especially KPM in Klakah District and Kedungjajang District, has not been right on target. The inaccuracy of the target in this case shows that from the data obtained there are poor families who do not get the BPNT program from the Government. Constraints faced in the implementation of Non-Cash Food Assistance (BPNT) disbursement of aid that is not in accordance with the specified time or experiencing delays in disbursement Keywords: Implementation, Non-Cash Food Aid, Beneficiary Families